Mismatch negativity eliciado por estímulo verbal e não verbal em adultos normo-ouvintes: um estudo de referências e comparações - Bruckmann, Mirtes (2017)
Objectives: To describe Mismatch Negativity (MMN) reference values in normal hearing adults with verbal and non-verbal stimuli and to compare them with each other, and also to compare ipsi and contralateral acoustic reflexes with the latency, amplitude and area of the MMN in all stimuli; to investigate values of latency, amplitude and area of the MMN with non-verbal stimulus with low contrast (standart stimulus: 750Hz and deviant stimulus: 1000Hz) and high contrast (standart stimulus: 750Hz and deviant stimulus: 4000Hz)and with verbal stimuli with low contrast standart stimulus: /da/ and deviant stimulus: /ta/) and high contrast (standart stimulus: /ba/ and deviant stimulus: /di/),identifying the most appropriate stimulus to determine the MMN potential; to identify the time of occurrence of MMN after the N1 in each of the stimuli and to compare values of latency, amplitude and area of MMN by gender in each of the stimuli. Methods: The subjects underwent anamnesis, meatoscopy, pure tone threshold audiometry, logoaudiometry, acoustic immitance measurements, dichotic sentences identification test and MMN. The MMN was performed with verbal stimuli of low and high contrast, being da/ta and ba/di respectively, and with non-verbal stimuli of low and high contrast, being of 750/1000Hz and 750/4000Hz respectively and with duration of non-verbal shorter than verbal stimuli. Results: Were evaluated 90 normal-hearing subjects with ages between 18 and 56 years of both genders. There was a difference in latencies, amplitudes and areas of all stimuli when compared to each other. The ipsilateral and contralateral acoustic reflexes did not influence the MMN in the different types of stimuli. Of the 90 subjects, 78 elicited the MMN with the da/ta stimulus, 73 with the stimulus of 750/1000Hz, 49 to 750/4000Hz and only 17 to ba/di. The stimulus of da/ta presented the highest latency, being farther from N1. Regarding gender, there was a significant difference only in the latency of the da/ta stimulus. Conclusion: It was possible to perform MMN on the SmartEP equipment in normal hearing adults and to describe reference values for verbal and non-verbal stimuli of different contrasts, which showed differences between them in terms of latency, amplitude and area. The ispi and contralateral acoustic reflexes did not influence the responses of the MMN. It was evidenced that the stimuli da/ta and 750/1000Hz were the most eliciting MMN in the population of normal hearing adults, confirming what the literature suggests about the use of lower contrast. Moreover, the verbal stimulus of da/ta presented better tracing morphology than non-verbal stimuli, probably due to the longer duration of the stimuli, as recommended by the literature. The labeling of the low contrast stimuli proved to be more distant from N1 compared to the higher contrast stimuli. The higher contrast stimuli, consisting of ba/di and 750/4000Hz, were the stimuli that elicited the MNN, demonstrating that they were still confusing in the marking, considering the presence of two negative peaks in the resulting wave, which could be confused with hearing pathway immaturity or the N1.Among genders there was difference only to the latency of da/ta verbal stimulus.